MXene-based composite material, preparation method and application thereof, and sodium ion battery
By using MXene-based composite materials in sodium ion battery electrode materials, including single-layer MXene and loaded metal element particles, the problem of insufficient battery capacity and cycling stability is solved, and higher electrochemical performance and flexibility are achieved.
Patent Information
- Application Number
- CN202411941588.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-28
AI Technical Summary
The performance improvement of sodium ion batteries, especially their capacity and cycle stability, still faces major challenges, mainly due to the poor conductivity and unstable chemical properties of the electrode materials.
MXene-based composite material is used, which includes a single layer of MXene-based material and metal element particles loaded on the surface of a single layer of MXene-based material. By uniformly modifying the transition metal element particles on the surface of the MXene material, the electrochemical reaction interface is increased, and the sodium storage capacity and conductivity are improved.
It effectively improves the capacity and cycle stability of sodium ion batteries, while enhancing the flexibility of electrode materials, adapting to the needs of multiple scenarios.
Smart Images

Figure CN119725477A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of new energy storage electrode materials, and in particular to a MXene-based composite material, a preparation method and application thereof, and a sodium ion battery. Background Art
[0002] Energy storage technology is the key to promoting the efficient use of renewable energy. As a supplement to lithium-ion batteries, sodium-ion batteries have attracted widespread attention in the field of energy storage in recent years due to their advantages such as abundant resources, low cost, high safety and excellent performance in low temperature environments. The application fields of sodium-ion batteries are constantly expanding, covering many applications such as low-speed electric vehicles, electric ships, home energy storage systems and industrial energy storage. However, the performance improvement of sodium-ion batteries, especially their capacity and cycle stability, still faces major challenges. As the decisive factor of battery performance, the development and optimization of electrode materials have become a key link in the industrialization process of sodium-ion batteries. Although transition metal materials are considered to be one of the most promising sodium-ion electrode materials due to their high capacity, fast metal ion transfer rate and structural stability, their inherent defects such as poor conductivity and unstable chemical properties limit their wide application in the field of electrochemistry. Solving this problem is the key to the high performance and large-scale application of sodium-ion battery electrode materials.
[0003] MXene materials, an emerging two-dimensional inorganic compound nanomaterial, are composed of transition metal carbides, nitrides or carbonitrides, and show good electrical conductivity, thermal conductivity, mechanical properties and chemical stability, providing new ideas for the design of electrode materials. In particular, MXene materials have hydroxyl groups or terminal oxygen on the surface, and the above structural characteristics make them have the metallic conductivity of transition metal carbides, which makes MXene an ideal carrier for transition metal materials, and it is expected to greatly improve the conductivity, reactivity and structural stability of sodium ion battery electrodes through composite structures.
[0004] However, the strong van der Waals interactions and hydrogen bonds between the layers of the MXene layered structure make it very easy for the MXene material to agglomerate and accumulate during the film formation process. Especially in the process of combining with metal ions, the metal material cannot be evenly modified on the surface of the MXene material, which seriously limits the full wetting of the electrolyte and hinders the transmission of metal ions, and also greatly reduces the electrochemical performance of sodium ion batteries.
[0005] This invention is proposed to improve the capacity, cycle stability and flexibility of electrode materials of sodium ion batteries and to open up a new path for the high performance and large-scale industrial application of sodium ion batteries. Summary of the invention
[0006] The main purpose of the present invention is to provide a MXene-based composite material, a preparation method and application thereof, and a sodium ion battery, so as to improve the capacity, cycle stability and flexibility of the sodium ion battery and to open up a new path for the high performance and large-scale industrial application of sodium ion batteries.
[0007] The MXene-based composite material includes a monolayer MXene-based material and metal particles loaded on the surface of the monolayer MXene-based material; wherein the metal is a transition metal. The MXene-based composite material proposed by the present invention can not only improve the problem of low electrochemical active surface area of transition metal, but also effectively increase the electrochemical reaction interface in the composite material, so that more sodium storage active sites are exposed to the material, and effectively improve the sodium storage capacity and conductivity of the MXene-based composite material. In addition, the composite material also has good flexibility. When the above material is applied to sodium ion batteries, the capacity and cycle stability of sodium ion batteries can be effectively improved.
[0008] Furthermore, the metal element is at least one of cobalt, iron and nickel; preferably, the thickness of the MXene-based composite material is 10 to 100 μm; preferably, the particle size of the metal element particles is 2 to 200 nm; preferably, the weight content of the metal element particles in the MXene-based composite material is 22 to 80.2%; preferably, the surface density of the MXene-based composite material is 0.05 to 10 mg / cm 2 The above characteristics can make MXene-based composite materials have better battery capacity and cycle stability when used in sodium-ion batteries.
[0009] Furthermore, the thickness of the MXene-based composite film is 30 to 50 μm; preferably, the particle size of the metal element particles is 2 to 100 nm; preferably, the weight content of the metal element particles in the MXene-based composite material is 36 to 68 wt%; preferably, the surface density of the MXene-based composite material is 1.5 to 6 mg / cm 2 When the MXene-based composite materials with the above characteristics are applied to sodium-ion batteries, the battery capacity and cycle stability of sodium-ion batteries can be further improved.
[0010] According to another aspect of the present invention, a method for preparing a MXene-based composite material is also provided, and the preparation method comprises the following steps: a single-layer MXene material, a soluble metal compound and a first portion of an organic solvent are first mixed to obtain a premixed solution A; the first mixing is stirring; the second portion of the organic solvent is added to the premixed solution A, and a second mixing is performed to obtain a premixed solution B; the premixed solution B is then centrifuged and washed to obtain a mixed solution; the second mixing is heating and stirring under a first protective gas atmosphere; the mixed solution is filtered to form a film to obtain a MXene-based composite material precursor; the MXene-based composite material precursor is dried and sintered to obtain a MXene-based composite material, wherein the sintering is performed under a second protective gas atmosphere. The above preparation method can make the metal element in the MXene-based composite material evenly distributed in the material, greatly improving the conductivity of the electrode material, and thus helping to improve the comprehensive performance of the sodium ion battery.
[0011] Furthermore, the volume of the second part of the organic solvent added is 20-50% of the first part of the organic solvent; preferably, in the second mixing process, ethylenediamine is also added thereto; preferably, the amount of ethylenediamine added is 0.5-2% of the volume of the premixed solution B; preferably, the first protective gas is at least one of nitrogen or argon; preferably, the concentration of the soluble metal compound in the premixed solution A is 10-40 mmol / L, and the concentration of the single-layer MXene material is 0.5-5 mg / mL. When preparing MXene-based composite materials, controlling the preparation parameters within the above range can make the electrochemical performance of the prepared MXene-based composite materials better.
[0012] Furthermore, the stirring time during the first mixing is 8 to 12 hours; preferably, the temperature of heating and stirring during the second mixing is 60 to 90°C, the time is 14 to 20 hours, and the speed during heating and stirring is 300 to 600 rpm; preferably, the centrifugal speed is 300 to 1000 rpm, and the centrifugal time is 2 to 4 minutes; preferably, the washing solvent during washing is one or more of methanol, ethanol, NN dimethylformamide, ethylenediamine and isopropanol; preferably, the number of washing times is 3 to 5 times.
[0013] Furthermore, an organic filter membrane is used for suction filtration and membrane formation; preferably, the organic filter membrane is at least one of a polytetrafluoroethylene filter membrane, a polytetrafluoroethylene filter membrane, a nylon filter membrane, a glass fiber filter membrane and a polypropylene filter membrane; preferably, the pore size of the organic filter membrane is 0.1 to 0.8 μm; more preferably, the pore size of the organic filter membrane is 0.4 to 0.6 μm; preferably, the suction filtration pressure is controlled to be 0.07 to 0.1 MPa during the suction filtration and membrane formation operation. The above conditions can further improve the electrochemical performance of the prepared MXene-based composite material.
[0014] Furthermore, the drying process is heated to 60-90°C at a heating rate of 10-20°C / min, and then kept warm for drying for 8-16h; the sintering process is heated to 500-900°C at a heating rate of 1-10°C / min, and then kept warm for sintering for 2-12h; preferably, the drying process is heated to 60-80°C at a heating rate of 10-20°C / min, and then kept warm for drying for 8-12h; the sintering process is heated to 600-800°C at a heating rate of 2-5°C / min, and then kept warm for sintering for 4-6h; preferably, the second protective gas is selected from N 2 , Ar and Ar / H 2 At least one of the mixed gases; preferably, the flow rate of the second protective gas is 0.05-0.1 L / min; preferably, the drying is carried out under vacuum conditions; preferably, the soluble metal compound is at least one of cobalt salts, iron salts, and nickel salts; preferably, the cobalt salt is one or more of cobalt nitrate, cobalt chloride, and cobalt acetate; the iron salt is one or more of iron nitrate, iron chloride, and iron sulfate; the nickel salt is one or more of nickel nitrate, nickel chloride, and nickel acetate; preferably, the organic solvent is one or more of ethylenediamine, isopropanol, N,N-dimethylformamide, methanol, ethanol, ammonia water, and tetrahydrofuran. When preparing MXene-based composite materials, controlling the preparation parameters within the above range can make the comprehensive performance of the prepared MXene-based composite materials better.
[0015] According to another aspect of the present invention, an electrode plate is provided, wherein the material of the electrode plate is the above-mentioned MXene-based composite material; or, the electrode plate is the MXene-based composite material prepared by the above-mentioned preparation method. The thickness of the electrode plate is 10 to 100 μm, and the surface density of the MXene-based composite material is 0.05 to 10 mg / cm 2 The metal weight content in the MXene-based composite material is 22 to 80.2%; preferably, the thickness of the electrode plate is 30 to 50 μm, and the surface density of the MXene-based composite material is 1.5 to 6 mg / cm 2 The weight content of metal in the MXene-based composite material is 36-68%. Using the above MXene-based composite material or the MXene-based composite material prepared by the above preparation method as an electrode plate can improve the comprehensive performance of the battery.
[0016] According to a fourth aspect of the present invention, a sodium ion battery is further provided, wherein the electrode plate is used as the negative electrode of the sodium ion battery. Using the electrode plate for the sodium ion battery can improve the battery capacity and cycle stability of the sodium ion battery, and the flexibility of the electrode plate opens up new ideas for the application scenarios of the sodium ion battery.
[0017] The present invention provides a MXene-based composite material, which includes a single-layer MXene-based material and metal particles loaded on the surface of the single-layer MXene-based material; wherein the metal is a transition metal. The present invention can effectively overcome the problem of the interaction between layers when the metal nanoparticles and MXene are composited by uniformly modifying the transition metal particles on the surface of the single-layer MXene nanosheet. In addition, the single-layer MXene is a two-dimensional nanostructure, and the transition metal is loaded on the surface of the single-layer MXene material. On the one hand, the ion transmission channels in the material are greatly enriched, which greatly improves the conductivity and cycle stability of the electrode material; on the other hand, under the synergistic effect of the transition metal and the MXene material in the MXene-based composite material, the electrochemical reaction interface in the material is increased, so that more sodium storage active sites are exposed in the material, and its sodium storage capacity is increased, thereby further improving the capacity and cycle stability of the sodium ion battery. In addition, the MXene-based composite material proposed by the present invention also has good flexibility, and when it is used as an electrode plate of a sodium ion battery, it can adapt to the application requirements of multiple scenarios. In summary, applying the MXene-based composite materials proposed in the present invention to sodium-ion batteries can effectively improve the battery capacity and cycle stability of sodium-ion batteries, and can also make the sodium-ion batteries have good flexibility, providing new ideas and new methods for the development of sodium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0019] Figure 1 The morphology of the MXene-based composite material prepared in Example 1 of the present invention is shown;
[0020] Figure 2 The X-ray diffraction pattern of the MXene-based composite material prepared in Example 1 of the present invention is shown;
[0021] Figure 3 The magnetization curve of the MXene-based composite material prepared in Example 1 of the present invention is shown.
[0022] Figure 4 The SEM image of the MXene-based composite material prepared in Example 1 of the present invention is shown;
[0023] Figure 5 A transmission electron microscope image of a single-layer MXene material in Example 1 of the present invention is shown;
[0024] Figure 6The transmission electron microscope image of the MXene-based composite material prepared in Example 1 of the present invention is shown. DETAILED DESCRIPTION
[0025] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0026] As described in the background technology section, one of the bottlenecks in the current industrial development of sodium-ion batteries is the lack of high-performance electrode materials. Improving the capacity, cycle stability and flexibility of sodium-ion batteries and opening up new paths for the high performance and large-scale industrial application of sodium-ion batteries are issues that need to be urgently addressed.
[0027] In order to solve the above problems, the present invention provides a MXene-based composite material, which includes a single-layer MXene-based material and metal element particles loaded on the surface of the single-layer MXene-based material; wherein the metal element is a transition metal element.
[0028] Different from the method of modifying MXene materials using compounds such as transition metal oxides, nitrides and carbides, the MXene-based composite material in the present invention introduces a transition metal element into a monolayer MXene to achieve the modification of the monolayer MXene material by the transition metal element. On the one hand, the modification of the monolayer MXene material by the transition metal element overcomes the van der Waals force and hydrogen bond force between layers when using multilayer MXene materials, and realizes the uniform modification of the transition metal element on the surface of the monolayer MXene nanosheet. The uniform introduction of the transition metal element can improve the electrochemical performance of the MXene-based composite material under the action of the spin space charge energy storage mechanism, thereby improving the battery capacity and cycle stability of the sodium ion battery. On the other hand, the composite of the transition metal element and the monolayer MXene material can not only give play to the advantages of the high capacity of the transition metal element, fast ion transmission speed, no volume change and good stability when used as an electrode material in the battery process, but also further give play to the advantages of the high conductivity, strong mechanical strength and mechanical stability of the monolayer MXene material. Under the synergistic effect of the two, not only can the problem of low electrochemical active surface area of transition metal elements be improved, but also the electrochemical reaction interface in the composite material can be effectively enlarged, so that more sodium storage active sites are exposed in the material, and the sodium storage capacity and conductivity of the MXene-based composite material are effectively improved. When the MXene-based composite material obtained by compounding a single-layer MXene material and a transition metal element is applied to a sodium-ion battery, the capacity and cycle stability of the sodium-ion battery can be effectively improved. In addition, the MXene-based composite material containing a MXene substrate has good flexibility. When it is used as an electrode plate of a sodium-ion battery, it can enable the sodium-ion battery to adapt to multiple scenarios and further broaden the application scenarios of MXene-based composite materials.
[0029] In a preferred embodiment, the metal element is at least one of cobalt, iron and nickel; the use of transition metal elements to modify a single layer of MXene-based materials can make the MXene-based composite material have the advantages of good conductivity, sodium storage capacity and good flexibility. When cobalt, iron and nickel among the transition metal elements are selected as the metal on the surface of the MXene-based composite material, the above effects are better. Preferably, the thickness of the MXene-based composite material is 10 to 100 μm; preferably, the particle size of the metal element particles is 2 to 200 nm; preferably, the weight content of the metal element particles in the MXene-based composite material is 22 to 80.2%; preferably, the surface density of the MXene-based composite material is 0.05 to 10 mg / cm 2By controlling the thickness of the MXene-based composite material, the weight content of the loaded metal particles, and the particle size of the metal particles within the above range, the MXene-based composite material can have better electron transmission performance, sodium storage performance, and flexibility, and further improve the capacity, cycle stability, and flexibility of the sodium-ion battery.
[0030] In a preferred embodiment, the thickness of the MXene-based composite film is 30 to 50 μm; preferably, the particle size of the metal element particles is 2 to 100 nm; preferably, the weight content of the metal element particles in the MXene-based composite material is 36 to 68 wt%; preferably, the surface density of the MXene-based composite material is 1.5 to 6 mg / cm 2 By controlling the thickness of the MXene-based composite material, the weight content of the loaded metal particles, and the particle size of the metal particles within the above ranges, the capacity, cycle stability, and flexibility of the sodium ion battery can be better.
[0031] According to another aspect of the present invention, a method for preparing the above-mentioned MXene-based composite material is also provided, and the preparation method comprises the following steps: a single-layer MXene material, a soluble metal compound and a first part of an organic solvent are first mixed to obtain a premixed solution A; the first mixing is stirring; the second part of the organic solvent is added to the premixed solution A for a second mixing to obtain a premixed solution B; the premixed solution B is then centrifuged and washed to obtain a mixed solution; the second mixing is heating and stirring under a protective gas atmosphere; the mixed solution is filtered to form a film to obtain a MXene-based composite material precursor; the MXene-based composite material precursor is dried and sintered to obtain a MXene-based composite material, wherein the sintering is carried out under a second protective gas atmosphere.
[0032] Specifically, in the preparation method of the MXene-based composite material of the present invention, the monolayer MXene material, the soluble metal compound and the first part of the organic solvent are stirred and mixed to obtain a premixed solution A. This process can fully mix the monolayer MXene material and the soluble metal compound. Then the obtained premixed solution A is heated and stirred with the second part of the organic solvent under a protective gas atmosphere to obtain a premixed solution B. The addition of the second part of the organic solvent and the heating and stirring operations can make the monolayer MXene material and the soluble metal compound better dispersed, and the components can be more fully mixed in the second mixing process. The monolayer MXene material can be more evenly dispersed and loaded with metal ions. Performing the above operation under a protective gas atmosphere can avoid the oxidation of the monolayer MXene material during the heating and stirring process. Then the obtained premixed solution B is centrifuged and washed to obtain a mixed solution, and then filtered to form a film to obtain a MXene-based composite material precursor; finally, the obtained MXene-based composite material precursor is dried and sintered under a second protective gas atmosphere to obtain a MXene-based composite material.
[0033] When metal ions are introduced into multilayer MXene materials, due to the strong van der Waals interaction and hydrogen bonding forces between layers in the layered structure of the multilayer MXene material, the multilayer MXene material and the metal ions are very likely to agglomerate and accumulate during the combination process, and it is difficult to achieve uniform modification of the metal ions on the surface of the multilayer MXene two-dimensional nanomaterial. In the preparation method of the present invention, the metal ions in the soluble metal compound can be effectively loaded on the monolayer MXene material by fully mixing the monolayer MXene material and the soluble metal compound in an organic solvent. The loading process uses the monolayer MXene material as a framework, and the metal ions and the hydroxyl groups or terminal oxygen on the surface of the MXene material generate forces, so that it can be better and more evenly loaded on the monolayer MXene material. In addition, in the present invention, a single-layer MXene material is used as a support, and there is no need to overcome the chemical forces between the layers in the multilayer MXene material during the loading process, and it is not easy to agglomerate and accumulate, which can make the load more uniform.
[0034] Furthermore, the present invention obtains a transition metal ion / MXene self-supporting film composite material with a single-layer MXene material as a carrier substrate by a suction filtration film-forming method for a single-layer MXene material loaded with metal ions in a premixed solution, and a high degree of controllability of the transition metal ion loading is achieved in the process. In addition, the suction filtration film-forming method can not only make the thickness of the film in the film-forming process consistent, but also make the single-layer MXene material loaded with metal ions uniformly distributed on the film under the action of the pressure during suction filtration. Moreover, since the single-layer MXene material is a layered structure, it still has good ductility and film-forming properties after being loaded with metal ions and film-forming, and still maintains excellent flexibility after being dried and sintered at high temperature. The above-mentioned MXene-based composite material precursor is dried and then sintered under the second protective gas atmosphere to reduce the transition metal ions loaded on the MXene base to metal elements, and the resulting metal elements are still distributed in the MXene matrix in a uniform state.
[0035] In summary, the preparation method of the MXene-based composite material provided by the present invention is to prepare a transition metal single substance particle / MXene self-supporting film composite material with MXene material as a carrier substrate by mixed loading and suction filtration film formation. The method can uniformly and effectively load the transition metal single substance on the MXene-based material, so that the obtained MXene-based composite material has more uniform and stable properties. The above two materials each having good performance are compounded, and the obtained material can effectively overcome the bottleneck of traditional materials in sodium ion batteries that are difficult to take into account capacity, stability and flexibility when applied to batteries, and provide new ideas for the development of sodium ion battery electrode materials. The transition metal single substance is uniformly modified on the surface of the single-layer MXene nanosheet layer, which effectively alleviates the layered stacking of MXene, provides abundant ion transmission channels, and greatly improves the conductivity of the electrode material. In addition, the preparation method is simple and controllable, and can be used for industrial-scale production.
[0036] Here, those skilled in the art should understand that during the centrifugation and washing process, the effective components in the premixed solution A will be partially lost. Therefore, the relative concentrations of the soluble metal compound and the monolayer MXene material in the premixed solution A can be adjusted according to the demand for the metal loading in the MXene-based composite material to prepare a MXene-based composite material that meets the requirements. For example, in the actual preparation process, the concentration of the mixed solution obtained after treatment can be measured to control the surface density and thickness of the MXene-based composite material within a preset range. The method for determining the concentration of the mixed solution includes: first taking FmL of the mixed solution and placing it in a container, weighing its mass as D mg, placing the container in a vacuum oven and heating and drying until the solvent is completely evaporated, and then weighing the container as E mg, the concentration of the mixed solution is: (DE) / F, and the thickness of the MXene-based composite material during the filtration process can be determined according to the calculated concentration of the mixed solution, so as to obtain a MXene-based composite material that meets the requirements.
[0037] In a preferred embodiment, the volume of the second part of the organic solvent added is 20-50% of the first part of the organic solvent. When preparing the premix solution B, the second part of the organic solvent is added to make the system mix better. In the actual operation process, there is no strict limit on the amount of the second part of the organic solvent added. The volume of the second part of the organic solvent added is controlled to be 20-50% of the first part of the organic solvent, so that the system can be mixed well. Preferably, in the second mixing process, it also includes adding ethylenediamine thereto; preferably, the amount of ethylenediamine added is 0.5-2% of the volume of the premix solution B. In the second mixing process, the above amount of ethylenediamine is added. On the one hand, ethylenediamine, as a reducing agent, can further prevent the MXene material from oxidizing and deteriorating (MXene material is easily oxidized when heated). On the other hand, the lone pair of electrons on nitrogen can form a stable complex with metal ions, which is conducive to the subsequent calcination step to better produce metal particles. Preferably, the concentration of the soluble metal compound in the premix solution A is 10-40mmol / L, and the concentration of the monolayer MXene material is 0.5-5mg / mL. When preparing MXene-based composite materials, controlling the concentration of soluble metal compounds and the concentration of single-layer MXene materials within the above range can be more conducive to controlling the electrochemical properties of the prepared MXene-based composite materials to be better.
[0038] In a preferred embodiment, the stirring time during the first mixing is 8 to 12 hours; preferably, the temperature of the heating and stirring during the second mixing is 60 to 90°C, the time is 14 to 20 hours, and the speed during the heating and stirring is 300 to 600 rpm; preferably, the first protective gas during the heating and stirring is at least one of nitrogen and argon. When the monolayer MXene material, the soluble metal compound and the organic solvent are mixed, the combination of pre-stirring and heating and stirring can make the mixing more uniform, which is conducive to the metal ions being more uniformly and effectively loaded on the monolayer MXene material. After the monolayer MXene material, the soluble metal compound and the organic solvent are mixed, the resulting mixed solution is subjected to centrifugation and washing operations in sequence, wherein the centrifugal speed during the above operation is controlled to be 300 to 1000 rpm, and the centrifugal time is 2 to 4 minutes; during the washing process, preferably, the washing solvent during washing is one or more of methanol, ethanol, NN dimethylformamide, ethylenediamine and isopropanol; preferably, the number of washings is 3 to 5 times. Controlling the operating conditions within the above range during the centrifugation and washing treatment can further make the premixed solution more uniformly mixed.
[0039] In a preferred embodiment, an organic filter membrane is used for suction filtration and membrane forming operation; preferably, the organic filter membrane is at least one of a polytetrafluoroethylene filter membrane, a polytetrafluoroethylene filter membrane, a nylon filter membrane, a glass fiber filter membrane and a polypropylene filter membrane. The above-mentioned organic filter membrane can better obtain the effective ingredients in the premixed solution during the suction filtration process. Preferably, the pore size of the organic filter membrane is 0.1-0.8 μm; preferably, the suction filtration pressure is controlled to be 0.07-0.1 MPa during the suction filtration and membrane forming operation. Controlling the pore size and suction filtration pressure of the organic filter membrane within the above range can make the suction filtration effect better. More preferably, the pore size of the organic filter membrane is 0.4-0.6 μm; the filter membrane under the above pore size has a better suction filtration effect. In addition, there is no restriction on the suction filtration device during suction filtration, and any device that can achieve the suction filtration purpose of the present invention, such as a glass suction filtration device series, a stainless steel suction cup series, a stainless steel single-layer series and a stainless steel positive pressure series, can be used. Parameters such as the diameter of the filter membrane during suction filtration can be specifically selected according to actual conditions.
[0040] In a preferred embodiment, the drying process is heated to 60-90°C at a heating rate of 10-20°C / min, and then kept warm for drying for 8-16 hours; the sintering process is heated to 500-900°C at a heating rate of 1-10°C / min, and then kept warm for sintering for 2-12 hours; controlling the drying and sintering temperatures within the above range can make the obtained MXene-based composite material have better performance. Preferably, the drying process is heated to 60-80°C at a heating rate of 10-20°C / min, and then kept warm for drying for 8-12 hours; the sintering process is heated to 600-800°C at a heating rate of 2-5°C / min, and then kept warm for sintering for 4-6 hours. Controlling the drying and sintering processes within the above preferred range can make the performance of the obtained MXene-based composite material better. The sintering process is carried out under the second protective gas atmosphere, which can better convert the transition metal ions in the MXene-based composite material precursor into metal elements. Preferably, the second protective gas is selected from N 2 , Ar and Ar / H 2 At least one of the mixed gases; preferably, the flow rate of the second protective gas is 0.05-0.1 L / min. Using the above second protective gas and controlling the flow rate of the second protective gas within the above range will achieve better drying and sintering effects. 2 When the mixed gas is used as the second protective gas atmosphere, control the Ar and H 2 The volume ratio of MXene-based composite materials is preferably 90%:10%. Preferably, the drying is performed under vacuum conditions, which can further prevent the transition metal ions in the MXene-based composite material precursor from being oxidized into metal oxides.
[0041] In a preferred embodiment, the soluble metal compound is at least one of a cobalt salt, an iron salt, and a nickel salt; the transition metal salt compound has good solubility and is more conducive to mixing with a monolayer MXene material. By way of example but not limitation, the cobalt salt is one or more of cobalt nitrate, cobalt chloride, and cobalt acetate; preferably, the iron salt is one or more of ferric nitrate, ferric chloride, and ferric sulfate; preferably, the nickel salt is one or more of nickel nitrate, nickel chloride, and nickel acetate. The types of the above transition metal salts have better effects. Preferably, the organic solvent is one or more of ethylenediamine, isopropanol, N,N-dimethylformamide, methanol, ethanol, ammonia water, and tetrahydrofuran. The types of the above organic solvents can better dissolve, mix, and further modify the monolayer MXene and the soluble metal compound.
[0042] According to the third aspect of the present invention, there is also provided an electrode plate, which is a MXene-based composite material comprising a single-layer MXene-based material and transition metal single-substance particles loaded on the surface of the single-layer MXene-based material; or, the electrode plate is a MXene-based composite material prepared by the above-mentioned method for preparing a MXene-based composite material. The thickness of the above-mentioned electrode plate is 10 to 100 μm, and the surface density of the MXene-based composite material is 0.05 to 10 mg / cm 2 , the metal content in the MXene-based composite material is 22 to 80.2wt%. In particular, the MXene-based composite material prepared by the above-mentioned method for preparing a MXene-based composite material can be used as an electrode plate without further processing. First, the MXene-based composite material precursor after filtration and film formation has good flexibility. After drying and sintering, it can still maintain the original film-forming state and can be used as an electrode plate by simple cutting and trimming. Second, since the MXene-based composite material contains MXene base material, it has good conductive properties, and there is no need to further add conductive agents, adhesives, etc. to prepare electrode materials, and it can have excellent performance as an electrode plate. Preferably, the thickness of the electrode plate is 30 to 50 μm, and the surface density of the MXene-based composite material is 1.5 to 6 mg / cm 2 , the metal weight content in the MXene-based composite material is 36-68%. The material under the above conditions has better performance as an electrode plate.
[0043] According to a fourth aspect of the present invention, a sodium ion battery is also provided, which includes the above-mentioned electrode plate as the negative electrode of the sodium ion battery. The sodium ion battery has good battery capacity and cycle stability, and the flexibility of the electrode plate opens up new ideas for the application scenarios of the sodium ion battery.
[0044] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0045] It should be further explained here that the single-layer MXene material used in the embodiment is a single-layer MXene powder purchased from Enyan New Materials Technology Co., Ltd., in which the thickness of the MXene single layer is in the range of 1.5 to 2.3 nm; the surface density of the MXene-based composite material in the embodiment refers to the surface density of 1 cm 2The mass of the MXene-based composite material per area, this parameter can reflect the feasibility of MXene-based composite materials to achieve high-loading electrode materials; the method for determining the metal content in MXene-based composite materials is a magnetic measurement method. Specifically, the method for determining the metal content in the material includes: using the comprehensive physical property measurement system (PPMS) of Quantum Design, an American company, to perform an initial hysteresis loop test on the prepared MXene-based composite material. The test conditions are room temperature 300K and a constant electric field of 3T. The ratio of the measured value to the magnetic value of the pure transition metal material is the metal content in the composite material.
[0046] Example 1
[0047] The monolayer MXene powder was dissolved in 200 mL of isopropanol to a concentration of 1.25 mg / mL. Co(NO 3 ) 3 6H 2 O is dissolved in the above solution to make the concentration of the above soluble metal cobalt salt be 20mmol / L, and the above mixed solution is stirred at room temperature for 12h to obtain a black premixed solution A; 2mL of ethylenediamine and 48mL of isopropanol are added to the above black premixed solution A, and reflux heated and stirred under nitrogen protection conditions to obtain a premixed solution B, wherein the heating temperature is 80°C, the heating time is 16h, and the stirring speed during heating is 500rpm; the premixed solution B is centrifuged and washed to obtain a mixed solution; wherein the centrifugal speed is 1000rmp, the centrifugal time is 2min, the washing solvent is ethanol, and the number of washings is 3 times.
[0048] First, 10 ml of the mixed solution was weighed and placed in a glass culture dish. After weighing, it was placed in a vacuum oven and heated and dried at 100°C until the solvent was completely evaporated. It was then weighed a second time, and the mass concentration of the mixed solution was calculated to be 16 mg / mL.
[0049] The mixed solution was filtered to form a membrane to obtain a MXene-based composite material precursor, the filter membrane during filtration was a polytetrafluoroethylene filter membrane with a pore size of 0.45 μm, and the pressure during filtration was 0.1 MPa; the obtained MXene-based composite material precursor was placed in an oven and heated to 85°C at a heating rate of 10°C / min, and dried under vacuum for 12 hours; then heated to 500°C at a heating rate of 5°C / min, and then dried under Ar / H 2 Sintering for 6h in a mixed gas atmosphere (v:v = 90%:10%), Ar / H 2 The flow rate of the mixed gas was 0.05 L / min, and a thin film of MXene-based composite material was obtained with a thickness of 40 μm and an area density of 3.18 mg / cm 2The particle size of the metal particles on the loading surface is 50 to 100 nm.
[0050] The MXene-based composite material prepared as above was photographed to obtain its Figure 1 The morphological diagram shown. Figure 1 It can be seen that the obtained cobalt-loaded MXene-based composite material exhibits good mechanical flexibility, and its planar flexible bending can reach 180°, which can meet the preparation requirements of flexible sodium-ion batteries.
[0051] The MXene-based composite material prepared as above was subjected to an X-ray diffraction test to obtain an X-ray diffraction pattern of the MXene-based composite material. The results are as follows: Figure 2 As shown. Figure 2 It can be seen that the prepared MXene-based composite material exhibits an obvious diffraction broad peak of amorphous carbon on the (002) crystal plane, and two obvious peaks near 44.2° and 51.5° correspond to the face-centered cubic lattices of the (111) and (200) crystal planes of metallic cobalt (JCPDS15-0806), respectively, and there are no peak signals of other substances, indicating that the preparation method of the invention can prepare metal-loaded MXene-based composite materials with higher purity.
[0052] The magnetic properties of the MXene-based composite material prepared above were tested to obtain a magnetization curve of the MXene-based composite material. The results are as follows: Figure 3 As shown. Figure 3 It can be seen that the magnetization intensity of the MXene-based composite material is 60.6emu / g, showing obvious ferromagnetism. According to the saturation magnetization intensity of metal Co single substance of 136emu / g, it can be calculated that the metal Co content in the MXene-based composite material is 44.6wt%;
[0053] The MXene-based composite material prepared as above was subjected to scanning electron microscopy test to obtain the SEM image of the MXene-based composite material. The results are as follows: Figure 4 As shown. Figure 4 It can be clearly seen that the metal cobalt particles are evenly distributed on the surface of the MXene sheets, there are many reaction active sites, and the mutual stacking phenomenon between the MXene sheets is effectively improved.
[0054] The single-layer MXene material used in the above preparation process was tested by transmission electron microscopy to obtain a transmission electron microscopy image of the single-layer MXene material. The results are as follows: Figure 5 As shown. Figure 5 It can be seen that the single-layer MXene material has a relatively thin thickness, and its plane size is about 2 to 3 μm. The MXene-based composite material prepared above was subjected to transmission electron microscopy test to obtain the transmission electron microscopy test results of the MXene-based composite material. Figure 6 shown by Figure 6 It can be seen that the metal cobalt particles in the MXene-based composite material can be evenly dispersed on the surface of the MXene layer, and the particle size of the metal cobalt particles is in the range of 50 to 100 nm, especially Figure 5 By comparing the transmission electron micrographs of the single-layer MXene material in FIG, it can be seen that the loading effect is obvious, which further proves that the preparation method of the present invention can effectively load transition metal elemental particles on MXene-based materials.
[0055] Example 2
[0056] The difference between Example 2 and Example 1 is that the soluble metal compound is Fe(NO 3 ) 3 9H 2 O, the mass concentration of the mixed solution obtained after treatment was 16 mg / mL. The thickness of the thin film MXene-based composite material prepared after filtration was 40 μm, and the surface density was 3.04 mg / cm 2 The particle size of the metal particles on the loading surface is 30-100 nm. In addition, the content of metal Fe in the MXene-based composite material is 43.6 wt%.
[0057] Example 3
[0058] The difference from Example 1 is that the soluble metal compound is Ni(NO 3 ) 3 6H 2 O, and its concentration is 0.02mmol / mL. The mass concentration of the mixed solution obtained after treatment is 16.1mg / mL. The thickness of the thin film MXene-based composite material prepared after filtration is 40μm, and the surface density is 3.21mg / cm 2 The particle size of the metal particles on the loading surface is 30-100 nm. In addition, the content of metal Ni in the MXene-based composite material is 44.5 wt%.
[0059] Example 4
[0060] The monolayer MXene powder was dissolved in 200 mL of tetrahydrofuran to a concentration of 1.25 mg / mL. 2Dissolve in the above solution to make the concentration of the above soluble metal cobalt salt be 10mmol / L, stir the above mixed solution at room temperature for 12h to obtain a black premixed solution A; add 1.2mL of ethylenediamine and 40mL of tetrahydrofuran to the above black premixed solution A, reflux and stir under nitrogen protection to obtain a premixed solution B, wherein the heating temperature is 60°C, the heating time is 20h, and the stirring speed during heating is 300rpm; centrifuge and wash the premixed solution B to obtain a mixed solution, wherein the centrifugal speed is 1000rmp, the centrifugal time is 2min, the washing solvent is NN dimethylformamide, and the number of washings is 3 times.
[0061] First, 10 ml of the mixed solution was weighed and placed in a glass culture dish. After weighing, it was placed in a vacuum oven and heated and dried at 100°C until the solvent was completely evaporated. It was then weighed a second time, and the mass concentration of the mixed solution was calculated to be 9.2 mg / mL.
[0062] The mixed solution was filtered to form a membrane to obtain a MXene-based composite material precursor, the filter membrane during filtration was a nylon filter membrane with a pore size of 0.1 μm, and the pressure during filtration was 0.07 MPa; the obtained MXene-based composite material precursor was placed in an oven and heated to 90°C at a heating rate of 10°C / min, and dried under vacuum for 8 hours; then heated to 500°C at a heating rate of 1°C / min, and then dried under Ar / H 2 Sintering for 12h in a mixed gas atmosphere (v:v = 90%:10%), Ar / H 2 The flow rate of the mixed gas was 0.05 L / min, and a thin film of MXene-based composite material was obtained with a thickness of 38 μm and an area density of 1.83 mg / cm 2 The particle size of the metal particles on the loading surface is 50-100 nm. In addition, the content of metal Co in the MXene-based composite material is 22.1 wt%.
[0063] Example 5
[0064] The monolayer MXene powder was dissolved in 200 mL of isopropanol to a concentration of 1.25 mg / mL. 3 COO 2Co was dissolved in the above solution to make the concentration of the above soluble metal cobalt salt be 40mmol / L, and the above mixed solution was stirred at room temperature for 8h to obtain a black premixed solution A; 6mL of ethylenediamine and 100mL of isopropanol were added to the above black premixed solution A, and refluxed and stirred under nitrogen protection to obtain a premixed solution B, wherein the heating temperature was 90°C, the heating time was 14h, and the stirring speed during heating was 600rpm; the premixed solution B was centrifuged and washed to obtain a mixed solution, wherein the centrifugal speed was 300rmp, the centrifugal time was 4min, the washing solvent was ethylenediamine, and the number of washings was 5 times.
[0065] First, 10 ml of the mixed solution was weighed and placed in a glass culture dish. After weighing, it was placed in a vacuum oven and heated and dried at 100°C until the solvent was completely evaporated. It was then weighed a second time, and the mass concentration of the mixed solution was calculated to be 21.3 mg / mL.
[0066] The mixed solution was filtered to form a membrane to obtain a MXene-based composite material precursor, the filter membrane during filtration was a glass fiber filter membrane with a pore size of 0.8 μm, and the pressure during filtration was 0.1 MPa; the obtained MXene-based composite material precursor was placed in an oven and heated to 60°C at a heating rate of 20°C / min, and then kept warm and dried for 16 hours under vacuum conditions; then heated to 900°C at a heating rate of 10°C / min, and then kept warm and sintered for 12 hours in an Ar gas atmosphere with an Ar gas flow rate of 0.1 L / min to obtain a thin film MXene-based composite material with a thickness of 42 μm and a surface density of 4.16 mg / cm 2 The particle size of the metal particles on the loading surface is 80-200 nm. In addition, the content of metal Co in the MXene-based composite material is 80.2 wt%.
[0067] Example 6
[0068] The monolayer MXene powder was dissolved in 200 mL of ammonia water to make the concentration of the monolayer MXene 1.25 mg / mL. 3 ) 3 6H 2 O was dissolved in the above solution to make the concentration of the above soluble metal cobalt salt be 20mmol / L, and the above mixed solution was stirred at room temperature for 12h to obtain a black premixed solution A; 2mL of ethylenediamine and 48mL of isopropanol were added to the above black premixed solution A, and refluxed and stirred under nitrogen protection to obtain a premixed solution B, wherein the heating temperature was 80°C, the heating time was 16h, and the stirring speed during heating was 500rpm; the premixed solution B was centrifuged and washed to obtain a mixed solution, wherein the centrifugal speed was 1000rmp, the centrifugal time was 2min, the washing solvent was ethanol, and the number of washings was 3 times.
[0069] First, 10 ml of the mixed solution was weighed and placed in a glass culture dish. After weighing, it was placed in a vacuum oven and heated and dried at 100°C until the solvent was completely evaporated. It was then weighed a second time, and the mass concentration of the mixed solution was calculated to be 16.2 mg / mL.
[0070] The mixed solution was filtered to form a membrane to obtain a MXene-based composite material precursor, the filter membrane during filtration was a polytetrafluoroethylene filter membrane with a pore size of 0.4 μm, and the pressure during filtration was 0.1 MPa; the obtained MXene-based composite material precursor was placed in an oven and heated to 80°C at a heating rate of 10°C / min, and dried under vacuum for 6 hours; then heated to 600°C at a heating rate of 2°C / min, and then heated to 400°C under Ar / H 2 Sintering for 6h in a mixed gas atmosphere (v:v = 90%:10%), Ar / H 2 The flow rate of the mixed gas was 0.05 L / min, and a thin film of MXene-based composite material was obtained with a thickness of 41 μm and an area density of 3.23 mg / cm 2 The particle size of the metal particles on the loading surface is 50-100 nm. In addition, the content of metal Co in the MXene-based composite material is 45.3 wt%.
[0071] Example 7
[0072] Xene powder was dissolved in 200 mL of ammonia water to make the concentration of monolayer MXene 1.25 mg / mL. Co(NO 3 ) 3 6H 2 O was dissolved in the above solution to make the concentration of the above soluble metal cobalt salt be 20mmol / L, and the above mixed solution was stirred at room temperature for 12h to obtain a black premixed solution A; 2mL of ethylenediamine and 48mL of isopropanol were added to the above black premixed solution A, and refluxed and stirred under nitrogen protection to obtain a premixed solution B, wherein the heating temperature was 80°C, the heating time was 16h, and the stirring speed during heating was 500rpm; the premixed solution B was centrifuged and washed to obtain a mixed solution, wherein the centrifugal speed was 1000rmp, the centrifugal time was 2min, the washing solvent was ethanol, and the number of washings was 3 times.
[0073] First, 10 ml of the mixed solution was weighed and placed in a glass culture dish. After weighing, it was placed in a vacuum oven and heated and dried at 100°C until the solvent was completely evaporated. It was then weighed a second time, and the mass concentration of the mixed solution was calculated to be 16.2 mg / mL.
[0074] The mixed solution was filtered to form a membrane to obtain a MXene-based composite material precursor, the filter membrane during filtration was a polytetrafluoroethylene filter membrane with a pore size of 0.6 μm, and the pressure during filtration was 0.1 MPa; the obtained MXene-based composite material precursor was placed in an oven and heated to 60°C at a heating rate of 20°C / min, and dried under vacuum for 12 h; then heated to 80°C at a heating rate of 5°C / min, and then dried under Ar / H 2 Sintering for 4 h in a mixed gas atmosphere (v:v = 90%:10%), Ar / H 2 The flow rate of the mixed gas was 0.05 L / min, and a thin film of MXene-based composite material was obtained with a thickness of 40 μm and an area density of 3.21 mg / cm 2 The particle size of the metal particles on the loading surface is 50-100 nm. In addition, the content of metal Co in the MXene-based composite material is 43.9 wt%.
[0075] Example 8
[0076] The difference between Example 8 and Example 1 is that the thickness of the thin film MXene-based composite material prepared after filtration is 10 μm and the surface density is 0.7 mg / cm 2 The particle size of the metal particles on the loading surface is 50-100 nm. In addition, the content of metal Co in the MXene-based composite material is 44.6 wt%.
[0077] Example 9
[0078] The difference between Example 8 and Example 1 is that the thickness of the thin film MXene-based composite material prepared after filtration is 100 μm and the surface density is 6.4 mg / cm 2 The particle size of the metal particles on the loading surface is 50-100 nm. In addition, the content of metal Co in the MXene-based composite material is 44.6 wt%.
[0079] Example 10
[0080] The difference between Example 10 and Example 4 is that the thickness of the thin film MXene-based composite material prepared after filtration is 10 μm and the surface density is 0.05 mg / cm 2 In addition, it was tested that the content of metal Co in the MXene-based composite material was 22.1wt%.
[0081] Embodiment 11
[0082] The difference between Example 11 and Example 5 is that the thickness of the thin film MXene-based composite material prepared after filtration is 100 μm and the surface density is 10 mg / cm 2In addition, it was tested that the content of metal Co in the MXene-based composite material was 80.2wt%.
[0083] Example 12
[0084] The difference between Example 12 and Example 1 is that when preparing the premixed solution A, the concentration of the soluble metal cobalt salt is 32 mmol / L, and the mass concentration of the mixed solution obtained after treatment is 23.7 mg / mL. The thickness of the thin film MXene-based composite material prepared after filtration is 41 μm, and the surface density is 3.69 mg / cm 2 The particle size of the metal particles on the loading surface is 50-100 nm. In addition, the content of metal Co in the MXene-based composite material is 67.6 wt%.
[0085] Example 13
[0086] The difference between Example 13 and Example 1 is that when preparing the premixed solution A, the concentration of the soluble metal cobalt salt is 16 mmol / L, and the mass concentration of the mixed solution obtained after treatment is 12.4 mg / mL. The thickness of the thin film MXene-based composite material prepared after filtration is 40 μm, and the surface density is 2.97 mg / cm 2 The particle size of the metal particles on the loading surface is 50-100 nm. In addition, the content of metal Co in the MXene-based composite material is 36.7 wt%.
[0087] Embodiment 14
[0088] The difference between Example 14 and Example 1 is that the concentration of the monolayer MXene is 6 mg / mL, and the soluble metal cobalt salt Co(NO 3 ) 3 6H 2 The concentration of O was 5 mmol / L. The mass concentration of the mixed solution obtained after treatment was 11.5 mg / mL. The thickness of the thin film MXene-based composite material prepared after filtration was 43 μm and the surface density was 0.4 mg / cm 2 The particle size of the metal particles on the loading surface is 50-100 nm. In addition, the content of metal Co in the MXene-based composite material is 5.3 wt%.
[0089] Comparative Example 1
[0090] The difference from Example 1 is that the single-layer MXene solution with a concentration of 1.25 mg / ml is directly subjected to the film-forming operation by suction filtration. The thickness of the thin film MXene prepared after suction filtration is 39 μm, and the surface density is about 1.3 mg / cm 2 .
[0091] Comparative Example 2
[0092] The difference from Example 1 is that cobalt oxide powder (Jingding Nano New Materials, KG-Co 3 O 4 -80) to replace Co(NO 3 ) 3 6H 2 The thickness of the prepared thin-film MXene-based composite material is 40 μm and the surface density is 3.27 mg / cm 2 . After testing, Co in MXene-based composites 3 O 4 The content is 44.6wt%.
[0093] Comparative Example 3
[0094] The difference from Example 1 is that a multilayer MXene material is used to replace a single-layer MXene material. The mass concentration of the mixed solution obtained after treatment is 14.3 mg / mL. The thickness of the thin film MXene-based composite material prepared after filtration is 41 μm, and the surface density is 2.96 mg / cm 2 The particle size of the metal particles on the loading surface is 50-100 nm. The content of metal Co in the MXene-based composite material is calculated to be 30.7 wt% through magnetic testing.
[0095] The properties of the MXene-based composite materials prepared in Examples 1 to 14 and Comparative Examples 1 to 3, such as surface density, type of loaded metal, metal content, thickness and flexibility, are summarized. The results are shown in Table 1.
[0096] Regarding flexibility, it should be noted that the obtained MXene-based composite material was tested for plane flexibility and curvature. The test method is to lay the film material flat on a horizontal plane, fix one end of the film, slowly lift the other end to make it bend towards the fixed end of the film, and keep it for 10 seconds. The critical bending angle at the time of fracture is recorded by a protractor, that is, the curvature of the film material. This curvature parameter can reflect its flexibility. When the curvature is between 120 and 180°, its flexibility is defined as excellent; when the curvature is between 60 and 120°, its flexibility is defined as good; when the curvature is between 0 and 60°, its flexibility is defined as ordinary.
[0097] Table 1
[0098]
[0099]
[0100] The MXene-based composite materials prepared in Examples 1 to 14 and Comparative Examples 1 to 3 were cut to obtain circular MXene-based composite materials with a diameter of 12 mm, which were directly used as electrode sheets in the negative electrode of the sodium ion half-cell, and the relevant performance of the corresponding sodium ion battery was tested, and the results are shown in Table 2. The preparation method of the sodium ion half-cell is as follows:
[0101] Preparation of sodium ion half-cell: A CR-2032 stainless steel button battery case was used to assemble the sodium ion battery in an anhydrous and oxygen-free (water and oxygen content ≤ 0.01 ppm) argon-protected glove box. The cathode shell, MXene-based composite material, diaphragm, and electrolyte (purchased from Duoduo Reagent, model NC-019, specific composition: 1 M NaClO 4 in DMC:EC=1:1Vol%with5%FEC)1.0mol / L NaClO 4 EC: DMC = 1: 1 Vol% + 5.0% FEC), sodium sheet, gasket, negative electrode shell are assembled in sequence, and the device is sealed at a pressure of ≤ 0.5 MPa to obtain a sodium ion half-cell assembled from the electrode sheets prepared in Examples 1 to 14 and Comparative Examples 1 to 3. The NEWARE BTS-5V battery charge and discharge test system developed by NEWARE was used to perform 200 cycles of charge and discharge tests on the assembled sodium ion battery at a current density of 0.1 A / g.
[0102] The charge and discharge test process includes: at a current density of 0.1A / g and a voltage range of 0.01 to 3.0V, the electrochemical performance test of the sodium ion battery prepared above is carried out, the discharge specific capacity after 200 cycles is tested, and the capacity retention rate is calculated. Among them, the assembled button battery is discharged at a constant current (to obtain the first cycle discharge capacity), and the battery is fully charged with the same current. In this process, a solid electrolyte membrane is mainly formed, resulting in irreversible capacity loss, and then the battery is still discharged at the same constant current. At the same time, the discharge is recorded, that is, the second cycle discharge capacity. The capacity retention rate in this application refers to: the percentage of the discharge capacity of the sodium ion battery after 200 cycles of charge and discharge to the second cycle discharge capacity.
[0103] Calculation method of discharge specific capacity to discharge area capacity: discharge specific capacity × electrode sheet mass (electrode sheet surface density × electrode sheet area 1.13cm 2 ) / pole area 1.13cm 2 = discharge area capacity.
[0104] Table 2
[0105]
[0106] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:
[0107] In Examples 1 to 3, the thickness of the sodium ion battery pole piece and the loading of the metal element are similar. Although the first cycle discharge specific capacity in Example 3 is slightly lower due to the limitation of the properties of the metal Ni itself, the sodium ion batteries in Examples 1 to 3 all have a good capacity retention rate. In Examples 4 and 5, the thickness of the sodium ion battery pole piece is not much different, but because of its large metal loading, Example 5 shows a good first cycle discharge specific capacity and capacity retention rate, but the flexibility of the electrode pole piece in Example 5 is worse. In Examples 6 and 7, the thickness of the sodium ion battery pole piece and the loading of the metal element are controlled within a more preferred range, and the flexibility of the electrode pole piece and the overall performance of the battery such as the specific capacity and cycle stability are all within a good range.
[0108] In Example 8, although the metal loading of the electrode plate of the sodium ion battery is within a more preferred range, the thickness of the plate is only 10 μm, which belongs to the "high loading, thin electrode" electrode plate. The specific capacity and cycle stability are difficult to accurately reflect the performance of the sodium ion battery, so the "discharge area capacity after 200 cycles" is introduced. According to the data in the table, its discharge area capacity is poor, but its cycle stability is good. The electrode plate in the sodium ion battery of Example 10 is similar to the "high loading, thin electrode" electrode plate, but its metal loading is low, so its discharge area capacity and cycle stability are worse than those of Example 8, but its cycle stability is still in a good range.
[0109] In Examples 9 and 11, although the metal loading of the electrode plates of the sodium ion battery is within a more preferred range, the thickness of the plates is 100 μm, which belongs to the category of "high-load, thick electrode" electrode plates. The first-cycle discharge specific capacity of the two examples is acceptable, but its stability is slightly worse. In addition, due to the large metal loading of the electrode plates in Example 11, its flexibility is poor. In Examples 12 and 13, the thickness of the sodium ion battery plates and the loading of the metal element are controlled within a more preferred range, and the flexibility of the electrode plates and the overall performance of the battery, such as the specific capacity and cycle stability, are all within a good range. Due to its low metal loading, Example 14 has poor cycle stability and first-cycle discharge specific capacity of the sodium ion battery.
[0110] In Comparative Example 1, the electrode plate of the sodium ion battery is not loaded with metal elements, and the composition of the electrode plate is only a single layer of MXene material. Although the thickness of the electrode plate is not much different from that of Example 1, the capacity retention rate of the sodium ion battery is only 68%, which is quite different from that of Example 1. This shows that the stability of the sodium ion battery is poor when the electrode plate in Comparative Example 1 is used for the sodium ion battery. The difference between Comparative Example 2 and Example 1 is that the metal element Co loaded in Example 1 is adjusted to CO 3 O 4 , the stability of the sodium ion battery is much lower than that of Example 1, and the capacity retention rate is far from the standard. The difference between Comparative Example 3 and Example 1 is that a multilayer MXene material is used to replace the single-layer MXene material. Due to the limitation of the metal loading of the multilayer MXene material, the metal Co content in the MXene-based composite material prepared by this method is only 30.7wt%. In addition, it is speculated that the performance of the sodium ion battery in Comparative Example 3 is compared with that of the sodium ion battery in Example 4, although the metal loading of the electrode plate of the sodium ion battery in Example 4 is less, but the cycle stability of the battery in Comparative Example 3 is significantly worse.
[0111] In summary, using the MXene-based composite material proposed in the present invention as a lithium-ion electrode plate, the corresponding sodium-ion battery can exhibit a higher first-cycle discharge capacity and good cycle stability; and when the thickness of the electrode plate and the metal loading are controlled within a more preferred range, not only the electrode plate of the sodium-ion battery exhibits good flexibility, but the first-cycle discharge specific capacity and cycle stability of the sodium-ion battery will also be better.
[0112] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A MXene-based composite material, characterized in that: The MXene-based composite material comprises a single-layer MXene-based material and metal element particles loaded on the surface of the single-layer MXene-based material; wherein the metal element is a transition metal element.
2. The MXene-based composite material according to claim 1, characterized in that The metal element is at least one of cobalt, iron and nickel; Preferably, the thickness of the MXene-based composite material is 10 to 100 μm; Preferably, the particle size of the metal element particles is 2 to 200 nm; Preferably, the weight content of the metal element particles in the MXene-based composite material is 22 to 80.2%; Preferably, the surface density of the MXene-based composite material is 0.05 to 10 mg / cm 2 .
3. The MXene-based composite material according to claim 1 or 2, characterized in that The thickness of the MXene-based composite film is 30 to 50 μm; Preferably, the particle size of the metal element particles is 2 to 100 nm; Preferably, the weight content of the metal element particles in the MXene-based composite material is 36 to 68 wt %; Preferably, the surface density of the MXene-based composite material is 1.5 to 6 mg / cm 2 .
4. The method for preparing a MXene-based composite material according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: The monolayer MXene material, the soluble metal compound and the first portion of the organic solvent are first mixed to obtain a premixed solution A; the first mixing is stirring; adding the second portion of organic solvent to the premix solution A for second mixing to obtain a premix solution B; then centrifuging and washing the premix solution B to obtain a mixed solution; the second mixing is heating and stirring under the first protective gas atmosphere; The mixed solution is filtered to form a membrane to obtain a MXene-based composite material precursor; The MXene-based composite material precursor is dried and sintered to obtain the MXene-based composite material, wherein the sintering is performed under a second protective gas atmosphere.
5. The method for preparing the MXene-based composite material according to claim 4, characterized in that: The added volume of the second part of organic solvent is 20-50% of the first part of organic solvent; Preferably, the second mixing process further includes adding ethylenediamine thereto; preferably, the amount of ethylenediamine added is 0.5-2% of the volume of the premix solution B; Preferably, the first protective gas is at least one of nitrogen or argon; Preferably, the concentration of the soluble metal compound in the premixed solution A is 10 to 40 mmol / L, and the concentration of the single-layer MXene material is 0.5 to 5 mg / mL.
6. The method for preparing a MXene-based composite material according to claim 4, characterized in that: The stirring time during the first mixing is 8 to 12 hours; Preferably, the temperature of the heating and stirring during the second mixing is 60 to 90° C., the time is 14 to 20 hours, and the speed of the heating and stirring is 300 to 600 rpm; Preferably, the centrifugal speed is 300-1000 rpm, and the centrifugal time is 2-4 min; Preferably, the washing solvent during the washing is one or more of methanol, ethanol, N-dimethylformamide, ethylenediamine and isopropanol; Preferably, the washing times are 3 to 5 times.
7. The method for preparing a MXene-based composite material according to claim 4, characterized in that: Using an organic filter membrane to perform the suction filtration and film-forming operation; Preferably, the organic filter membrane is at least one of a polytetrafluoroethylene filter membrane, a polytetrafluoroethylene filter membrane, a nylon filter membrane, a glass fiber filter membrane and a polypropylene filter membrane; Preferably, the pore size of the organic filter membrane is 0.1 to 0.8 μm; More preferably, the pore size of the organic filter membrane is 0.4 to 0.6 μm; Preferably, when performing the suction filtration membrane forming operation, the pressure of the suction filtration is controlled to be 0.07-0.1 MPa.
8. The method for preparing a MXene-based composite material according to any one of claims 4 to 7, characterized in that: The drying process is to heat the material to 60-90°C at a heating rate of 10-20°C / min, and then keep the temperature for drying for 8-16h; the sintering process is to heat the material to 500-900°C at a heating rate of 1-10°C / min, and then keep the temperature for sintering for 2-12h; Preferably, the drying process is to heat the temperature to 60-80°C at a heating rate of 10-20°C / min, and then keep the temperature for drying for 8-12 hours; the sintering process is to heat the temperature to 600-800°C at a heating rate of 2-5°C / min, and then keep the temperature for sintering for 4-6 hours; Preferably, the second protective gas is selected from at least one of N2, Ar and Ar / H2 mixed gas; Preferably, the flow rate of the second protective gas is 0.05-0.1 L / min; Preferably, the drying is carried out under vacuum conditions; Preferably, the soluble metal compound is at least one of a cobalt salt, an iron salt, and a nickel salt; Preferably, the cobalt salt is one or more of cobalt nitrate, cobalt chloride and cobalt acetate; the iron salt is one or more of iron nitrate, iron chloride and iron sulfate; the nickel salt is one or more of nickel nitrate, nickel chloride and nickel acetate; Preferably, the organic solvent is one or more of ethylenediamine, isopropanol, N,N-dimethylformamide, methanol, ethanol, ammonia water and tetrahydrofuran.
9. An electrode plate, characterized in that: The material is the MXene-based composite material according to claim 1 or 2; or, The electrode plate is the MXene-based composite material obtained by the preparation method according to any one of claims 3 to 8; the thickness of the electrode plate is 10 to 100 μm, and the surface density of the MXene-based composite material is 0.05 to 10 mg / cm 2 , the metal weight content in the MXene-based composite material is 22 to 80.2%; Preferably, the thickness of the electrode plate is 30-50 μm, and the surface density of the MXene-based composite material is 1.5-6 mg / cm 2 , the metal weight content in the MXene-based composite material is 36 to 68%.
10. A sodium ion battery, characterized in that: The electrode sheet according to claim 9 is included as the negative electrode of the sodium ion battery.